Notch activation by phenethyl isothiocyanate attenuates its inhibitory effect on prostate cancer cell migration. - Su-Hyeong Kim; Anuradha Sehrawat; Kozue Sakao; Eun-Ryeong Hahm; Shivendra V Singh (PLoS ONE)
Phenethyl isothiocyanate (PEITC) is a promising cancer chemopreventive component of edible cruciferous vegetables with in vivo efficacy against prostate cancer in experimental rodents. Cancer chemopreventive response to PEITC is characterized by its ability to inhibit multiple oncogenic signaling pathways, including nuclear factor-κB, Akt, and androgen receptor. The present study demonstrates, for the first time, that PEITC treatment activates Notch signaling in malignant as well as normal human prostate cells. Exposure of human prostate cancer cells (LNCaP, PC-3, and DU145) and a normal human prostate epithelial cell line (PrEC) to PEITC resulted in cleavage (active form) of Notch1 and Notch2, and increased transcriptional activity of Notch. In PC-3 and LNCaP cells, PEITC treatment caused induction of Notch ligands Jagged1 and Jagged2 (PC-3), overexpression of γ-secretase complex components Presenilin1 and Nicastrin (PC-3), nuclear enrichment of cleaved Notch2, and/or up-regulation of Notch1, Notch2, Jagged1, and/or Jagged2 mRNA. PEITC-induced apoptosis in LNCaP and PC-3 cells was significantly attenuated by RNA interference of Notch2, but not by pharmacological inhibition of Notch1. Inhibition of PC-3 and LNCaP cell migration resulting from PEITC exposure was significantly augmented by knockdown of Notch2 protein as well as pharmacological inhibition of Notch1 activation. Nuclear expression of cleaved Notch2 protein was significantly higher in PC-3 xenografts from PEITC-treated mice and dorsolateral prostates from PEITC-fed TRAMP mice compared with respective control. Because Notch signaling is implicated in epithelial-mesenchymal transition and metastasis, the present study suggests that anti-metastatic effect of PEITC may be augmented by a combination regimen involving a Notch inhibitor.